DYNAMICS OF SETTLER COLONIALISM: INFLUENCING FACTORS ON THE ISRAELI TREATMENT TOWARDS THE PALESTINIANS - Belal Alakhras; Raja Noriza Raja Ariffin; Makmor Tumin, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
This essay explores the factors influencing the Israeli government’s treatment of the Palestinians in the West Bank and Gaza Strip between 2009 and 2019. The essay argues that the Israeli approach towards the Palestinians can be examined in the broader context of settler colonialism and is not exclusively shaped on a security basis. Sem-structured interviews, documents, and other secondary data sources were employed to determine factors defining Israel’s approach in confronting Palestinians. Multiple internal and external factors have shaped the Israeli treatment of Palestinians in the West Bank and Gaza Strip. Internal elements include power structure, ideology, public opinion, and the colonized people’s response. The external factors include the regional (dis-)order and the US-Israel alliance. This analysis finds that most of these factors have fuelled a violent Israeli treatment towards Palestinians. The Palestinian resistance was found to compel Israel to lessen its violent treatment on various occasions. These results indicate that the Israeli treatment of Palestinians is not exclusively shaped on a security basis.